“Vai buscar jongueiro aonde está, com o jongo temos que continuar”: um estudo da continuidade no jongo. - Alvarez, Iana Lopes (2019)
Jongo is a common dance in southeastern Brazil and performed by black groups or communities - urban or rural. It is recognized as a traditional practice in maintaining drumming, dancing, dress, song form and articulation, as well as bonding with ancestors - both to appropriate their knowledge and to greet them. The jongo was made Intangible Cultural Heritage of Brazil because it has the characteristics of “Afro-Brazilian cultural manifestation, which comprises the elements: dancing to the sound of drums and singing with magic-poetic elements” (Iphan, 2007). From materials elaborated on the jongo, with the Iphan Dossier, the historiographic and anthropological bibliography, I return to some elaborate themes, such as African acculturation and crossbreeding. These studies made important contributions to black culture approaches in Brazil, and generally formulated analyzes of the origins of jongo and its relationship with society. Supported by the community of Jongo de Piquete, located in Piquete - a city of the state of São Paulo, I propose to highlight other practitioners agencies to maintain the jongo, the intrinsic relations to its practice and what are the disagreements with the reference literature. Throughout the reflection, I suggest that continuity is a purpose that connects families, ancestors, drums and times, as relevant as the bonds they produce with their surroundings. This paper seeks to contribute to anthropological debates about traditional practices and communities.